Pengaruh Social Media Customer Engagement Dan Kepuasan Pelanggan Terhadap Loyalitas Merek Perguruan Tinggi Swasta - Roby Darmadi; Parlagutan Silitonga; Al AGus Kristiadi (Widya Manajemen, 2021)
The broader use of the internet and the behavior of social media users have a significant influence on business management and higher education. Communication and interaction between customers and the company become more open and faster. This study aims to analyze the effect of social media customer engagement and student and alumni satisfaction on college loyalty as a brand and the role of student and alumni satisfaction as a mediator. The research uses a survey method conducted on 220 students and alumni of a leading tourism college in Jakarta who are followers of the college's Instagram account. Analisis data using SEM (StructuralEquation Model) revealed the research results that social media customer engagement significantly influences increasing loyalty to the college. Student and alumni satisfaction significantly influences increasing loyalty to the college and being a mediator that significantly influences customer engagement towards student and alumni loyalty.